KAJIAN PENGUKURAN TINGKAT KEMATANGAN KEAMANAN SISTEM INFORMASI PADA PENGOLAHAN DATA ELEKTRONIK (PDE) MENGGUNAKAN FRAMEWORK COBIT 4.1 STUDI KASUS: SMK NEGERI 24 JAKARTA - Furnia Sari Dewi Kencanawati; Yahdi Kusnadi (LPPM Universitas Bina Sarana Informatika, 2011)
Electronic Data Processing (PDE) at SMK Negeri 24 Jakarta has a significant role in supporting the work processes as well as teaching and learning in schools. Its existence as one of the utilization of technology in the field of Information Technology (IT) has brought a new wind to the development progress of the inner workings of Administration (TU). However, the application of ICT, particularly PDE, in addition to bringing fresh air for IT development also brings the values that will lead to a negative thing if the awareness of IT security for each individual user's PDE is not maximized. Measuring the level of maturity on the PDE by using the COBIT framework 4.1 and domain DS5, Deliver and support system, are expected to provide information on the extent to which awareness of the security system on each user's information, measure the maturity level of information system security in PDE, to know the findings and constraints on system as well as members of the problem and alternative solutions based on the measurement results of the questionnaire results. Keywords: Electronic Data Processing (PDE), Measurement, Maturity, Security